ANALISIS FIQIH MUNAKAHAT DAN HAK ASASI MANUSIA TERHADAP PERKAWINAN PAKSA - Baidhawi, Qosim; Qomaruzzaman, Qomaruzzaman (Institut Agama Islam Negeri (IAIN) Pontianak, 2024)
This study aims to examine the interaction between Islamic marriage jurisprudence (fiqih munakahat) and human rights (HR) in the context of forced marriage in Indonesia. Using a qualitative research method, this approach involves a literature review and analysis of legal documents. A literature review will be conducted to gather various sources related to fiqh munakahat, human rights, and the practice of forced marriage. With this approach, the study is expected to produce new insights that are useful in efforts to effectively address the issue of forced marriage in accordance with the values of Islamic law and human rights. The results of the study show that forced marriage contradicts the basic principles of fiqh munakahat which emphasize the willingness and consent of both spouses, as well as with human rights standards that uphold individual freedom. Although fiqh and positive law in Indonesia prohibit the practice of forced marriage, challenges in its implementation remain, including cultural factors and misinterpretations. Therefore, a multidimensional approach that integrates the values of fiqh, positive law, and human rights is needed to address this issue comprehensively.